KEBERAGAMAN BUDAYA PAKAIAN ADAT KURUNG LABUH DAN TELUK BELANGA PROVINSI KEPULAUAN RIAU - Dian Cahya Anbiya; Syairul Bahar; Eva Nurharyati; Alya Hanifah Andriani; Fitria Difa Nuzula; Nooraniyah Karima Afifah; Farkhan Abdurochim Alfarauq (Triwikrama: Jurnal Ilmu Sosial, 2024)
This study aims to explore the cultural diversity of traditional clothing in the Riau Islands Province as part of the Malay cultural identity. Using qualitative methods through observation, interviews, and documentation, the study reveals the philosophical, symbolic, and functional meanings of traditional attire such as Kurung Labuh and Teluk Belanga. The findings indicate that traditional clothing not only represents Islamic values and social propriety but also serves as a symbol of preserving ancestral heritage amid modernization. This study highlights the importance of safeguarding traditional clothing as a culturally rich legacy.